The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1101/868000
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Compact attractors of an antithetic integral feedback system have a simple structure

Abstract: Since its introduction by Briat, Gupta and Khammash, the antithetic feedback controller design has attracted considerable attention in both theoretical and experimental systems biology. The case in which the plant is a twodimensional linear system (making the closed-loop system a nonlinear four-dimensional system) has been analyzed in much detail. This system has a unique equilibrium but, depending on parameters, it may exhibit periodic orbits. An interesting open question is whether other dynamical behaviors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In [38,39], the authors determined analytic conditions on the reaction rate parameters of the antithetic feedback network such that the linearized closed loop system is stable. Subsequent research also discussed the stability of the nonlinear dynamics of closed loop antithetic feedback network [44,45]. Without stability, the antithetic feedback control would not be able to track the reference signal; instead, it would oscillate indefinitely.…”
Section: A Mathematical Model Of Antithetic Feedback Network With Con...mentioning
confidence: 99%
See 1 more Smart Citation
“…In [38,39], the authors determined analytic conditions on the reaction rate parameters of the antithetic feedback network such that the linearized closed loop system is stable. Subsequent research also discussed the stability of the nonlinear dynamics of closed loop antithetic feedback network [44,45]. Without stability, the antithetic feedback control would not be able to track the reference signal; instead, it would oscillate indefinitely.…”
Section: A Mathematical Model Of Antithetic Feedback Network With Con...mentioning
confidence: 99%
“…Indeed, in the previous synthetic biological implementations of antithetic feedback in E. coli and S. cerevisiae, the antithetic feedback controller's relative steady-state error (as normalized to the reference) has been measured to be 5-50% [28,31]. Another consideration is the stability of the closed-loop antithetic feedback system since theoretical studies have demonstrated that, depending on the reaction rate parameters, the antithetic controller can become unstable and periodic oscillations can arise [39,42,44,45]. Therefore, it is important to consider how the stability, robustness, and steady-state error (performance) of the antithetic feedback motif depend on its synthetic biological implementation and to study in depth how to tune these properties [28,46].…”
Section: Introductionmentioning
confidence: 99%
“…As a final remark, even though the design framework we describe here is for circadian clocks, the approach presented is potentially applicable to tracking or restoring any biological system characterized by entrainable, periodic oscillations, for which theoretical developments are garnering great interest (see e.g., 58,59 ).…”
mentioning
confidence: 99%